A Self‐Assembled Plasmonic Substrate for Enhanced Fluorescence Resonance Energy Transfer. Issue 8 (14th January 2020) - Hou, Shuai; Chen, Yonghao; Lu, Derong; Xiong, Qirong; Lim, Yun; Duan, Hongwei
Abstract: Fluorescence resonance energy transfer (FRET) has found widespread uses in biosensing, molecular imaging, and light harvesting. Plasmonic metal nanostructures offer the possibility of engineering photonic environment of specific fluorophores to enhance the FRET efficiency. However, the potential of plasmonic nanostructures to enable tailored FRET enhancement on planar substrates remains largely unrealized, which are of considerable interest for high‐performance on‐surface bioassays and photovoltaics. The main challenge lies in the necessitated concurrent control over the spectral properties of plasmonic substrates to match that of fluorophores and the fluorophore–substrate spacing. Here, a self‐assembled plasmonic substrate based on polydopamine (PDA)‐coated plasmonic nanocrystals is developed to effectively address this challenge. The PDA coating not only drives interfacial self‐assembly of the nanocrystals to form closely packed arrays with customized optical properties, but also can serve as a tailored nanoscale spacer between the fluorophores and plasmonic nanocrystals, which collectively lead to optimized fluorescence enhancement. The biocompatible plasmonic substrate that allows convenient bioconjugation imparted by PDA has afforded improved FRET efficiency in DNA microarray assay and FRET imaging of live cells. It is envisioned that the self‐assembled plasmonic substrates can be readily integrated into fluorescence‐based platforms for diverse biomedical and photoconversion applications. Abstract : Plasmonic substrates for enhanced fluorescence resonance energy transfer (FRET) are fabricated by interfacial self‐assembly of polydopamine‐coated plasmonic nanocrystals. The plasmonic substrates with tailored spectral properties and optimized substrate–fluorophore spacing demonstrate greatly improved performance in the microarray assay of DNA and the FRET imaging on live cells, encouraging applications in other emerging fields, such as photovoltaics and artificial photosynthesis.